2012
DOI: 10.7589/2011-09-267
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Urbanization on Prevalence of Baylisascaris procyonis in Intermediate Host Populations

Abstract: ABSTRACT:Baylisascaris procyonis is an intestinal parasite of raccoons (Procyon lotor) that can also infect humans and a wide range of wildlife species. Prevalence of B. procyonis in raccoon populations appears to decrease as the landscape urbanizes, but less is known about prevalence in the small-mammal intermediate hosts of the parasite. We measured prevalence of B. procyonis in populations of mice (Peromyscus spp.) in forest preserves along a gradient of urbanization in Illinois. Prevalence in the mouse int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 15 publications
1
14
1
Order By: Relevance
“…For example, in a study of a fragmented forest along a gradient of urbanization (in Chicago, IL), the prevalence of B. procyonis in Peromyscus spp. was found to increase as human population density increased (67). Even though the opposite relationship was observed for raccoons, because of much higher densities of raccoons in urban environments, overall loads of infective B. procyonis eggs would still be very high and present a danger of transmission (67).…”
Section: Raccoons As Source Of Infectionmentioning
confidence: 93%
See 1 more Smart Citation
“…For example, in a study of a fragmented forest along a gradient of urbanization (in Chicago, IL), the prevalence of B. procyonis in Peromyscus spp. was found to increase as human population density increased (67). Even though the opposite relationship was observed for raccoons, because of much higher densities of raccoons in urban environments, overall loads of infective B. procyonis eggs would still be very high and present a danger of transmission (67).…”
Section: Raccoons As Source Of Infectionmentioning
confidence: 93%
“…was found to increase as human population density increased (67). Even though the opposite relationship was observed for raccoons, because of much higher densities of raccoons in urban environments, overall loads of infective B. procyonis eggs would still be very high and present a danger of transmission (67). Raccoon populations have increasingly been detected in densely populated and urbanized areas, such as Brooklyn, NY (31, 68), Atlanta, GA, Orange County, CA, Portland, OR, Chicago, IL, and Toronto, Ontario, Canada (61,69,70,71), showing the great adaptability of this species.…”
Section: Raccoons As Source Of Infectionmentioning
confidence: 99%
“…Page et al (2008) found that the prevalence of B. procyonis in raccoons in urban areas was lower than rural areas in the midwestern US despite high raccoon densities in urban areas, but Jacobson et al (1982) found no difference in prevalence between rural and urban areas in Indiana. In a more recent study, Kellner et al (2012) found that the prevalence of B. procyonis in intermediate hosts (Peromyscus sp.) was higher in urban than rural areas of Illinois.…”
Section: Introductionmentioning
confidence: 95%
“…In a study comparing prevalence across landscapes in Indiana, prevalence was higher in agriculture-dominated landscapes (28%) than in forest-dominated landscapes (6%), and across the entire landscape, prevalence increased predictably as a function of decreasing forested area and increasing isolation of patches (Page et al, 2001a). In a study of prevalence among white-footed mice in an urban landscape, overall prevalence among mice was 33%, and ranged from 17% to 42% increasing as a function of increasing human population density (Kellner et al, 2012). …”
Section: Transmission Dynamics Of B Procyonis In Human-dominated Lanmentioning
confidence: 99%
“…Latrines may thus become concentrated in forest patches throughout a variety of landscape types, and increases in transmission to paratenic hosts increase as a function of patch size and isolation (Page et al, 2001a). Even in urban landscapes, raccoons disproportionately visit forested patches (Bozek et al, 2007), and despite decreased prevalence of B. procyonis among raccoons (Page et al, 2009b) in some urban landscapes, prevalence of infection among paratenic hosts in the same landscape is increased (Kellner et al, 2012). This response suggests that potential paratenic hosts may be at increased risk of infection in landscapes that alter contact rates of raccoons and ultimately latrine densities.…”
Section: Transmission Dynamics Of B Procyonis In Human-dominated Lanmentioning
confidence: 99%